Service Quality and Customer Satisfaction: A Study of MyRapid in Malaysia - Joe Yee Ong; Wei Chee Ong; Ai Chyi Ong; Kai Qing On (AIBPM Publisher, 2022)
MyRapid is the dominant player in Malaysia's public transportation industry. It innovates and drives public transportation systems in the country while providing public transportation services such as light rail transit (LRT), monorail, and bus services to connect millions of people from different states. This paper examines if the service quality of the public transport services influences customer satisfaction in Penang, Malaysia. The five dimensions of service quality include assurance, empathy, reliability, responsiveness, and tangibles. A total of 150 MyRapid users participated in the survey. Findings revealed that the only two dimensions of service quality, which are reliability and tangibles were significantly related to customer satisfaction whereas the other three dimensions are not supported. The findings provide insight into the public transportation industry to improve the public transportation system in Malaysia, given that service quality is a critical driver of customer satisfaction.